Restraint of Overseas Personal Shopper as a Form of Legal Protection for Authorized Stores in Indonesia - Suweni Efrin (NORMA, 2021)
Nowadays, many business people use personal shopper because they also provide benefits in addition to being more effective and efficient. After all, the activities of designated personal shoppers are carried out without face to face. In different regions, this also creates many problems related to both parties' agreements in conduct buying and selling activities and how the validity of the deal that occurs between the two parties. The research method used is normative research method, which is based on the legislation and is carried out with a statutory approach, namely BW and Law Number 8 of 1999 concerning Consumer Protection. Based on the study results, it can be concluded that the agreement made between the two parties is only based on understanding. The agreement contained is generally anonymous, and the deal is obligatory. Second: The Government's way to control personal shopper services is based on the Consumer Protection Act if a violation of law is committed by one of the parties. Control efforts that the government can do are limited to guidance and supervision.Keywords: Personal Shopper, Agreements, Overseas